Regional Economic Integration Within the Context of International Economic Relations: A Literature Review in an International Context - Petkov, Filip (Research Papers, 2022)
The aim of the research is to present, critically analyse and summarize the main theoretic aspects of regional economic integration through the viewpoints of some major Bulgarian and foreign authors in the field. The object of the research are the main theories related to the regional economic integration while subject of this paper is to present their evolution, economic and political characteristics. To achieve these research objectives, three basic research tasks have been conducted: 1) the essence of regional integration has been analysed as a critical element in the system of the international economic relations; 2) definition of the concepts for regionalism and regionalization is provided; 3) the development of the old and the new regionalism has been presented, as well as the newest trends in regionalism. This research is limited within the field of theoretical analysis. The main thesis is proved by exploring the development of theories of regional economic integration. It shows a deepening of the relations between the participants – a clear result when comparing old and new regionalism, as relations develop not only in the field of trade and economic cooperation, but also in political aspect, where common strategic goals for greater cohesion are set to achieve greater coherence of the socio-economic systems. The research methods that have been used are comparative analysis, content analysis, and historical and logical analysis. The results of the research are theoretical generalisations that provide basis for taking theoretically based political decisions on further regional integration in an international context.